Proceedings of the Austrian Robotics Workshop 2018 - Zech, Phillipp; Piater, Justus (Austrian Robotics Workshop, 2018)
The sixth Austrian Robotics Workshop sought to bring together researchers, professionals and practitioners working on different topics in robotics to discuss recent developments and future challenges in robotics and its applications. The 2018 edition of the workshop series was held at the University of Innsbruck in May 2018. - Der sechste Austrian Robotics Workshop versammelte Forscher, Experten und in der Praxis Arbeitende, die sich mit verschiedenen Themen der Robotik auseinandersetzen, um über Entwicklungen und zukünftige Herausforderungen der Robotik und ihren Anwendungen zu diskutieren. Die 2018 stattgefundene Ausgabe der Workshop-Reihe fand an der Universität Innsbruck im Mai 2018 statt.